(untitled) (Journal of actual problems of jurisprudence, 2025)
This article comprehensively examines the legal regulation of flood prevention in the Republic of Kazakhstan. The study analyzes the content of normative legal acts related to floods, the clarity of legal terminology, and the interaction mechanisms and responsibilities between state authorities. Furthermore, the article explores international practices and climate adaptation strategies aimed at reducing flood risks. The authors argue that an effective and systematic approach is essential for managing the social, economic, and environmental consequences of floods at the legal level. The article identifies shortcomings in the current legislation and institutional framework and proposes solutions. Specifically, it recommends conducting a legislative inventory, compiling a full register of water bodies and hydraulic structures, and strengthening transboundary cooperation. The findings provide recommendations for improving legal policy and ensuring national water security. The article substantiates the relevance of enhancing Kazakhstan’s national flood prevention strategy through legal reforms and integrated risk management tools. This scientific article was prepared as part of the implementation of project AP26193915, “Legal Regulation of the Use and Safety of Hydraulic Structures under Conditions of Sustainable Development”, funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan. Keywords: Floods, legal regulation, water security, normative legal acts, hydraulic structures, climate adaptation.